Encyclopedia of neuroscience - Squire, Larry R. (Berlin: Elsevier, 2009)
Autonomic Nervous System; Communication, language and speech; Disease and Dysfunction; Evolution and Comparative Biology of Nervous Systems; History; Intercellular Communication; Methods and Techniques; Molecular and Cell Biology of Nervous Systems; Motor Neuromuscular System; Nervous System Development, Repair and Aging; Neural Basis of Behavior; Sensory Systems; Structural Organization of the Brain
Searchable encyclopedia; articles available as HTML previews and as PDF documents.
World Wide Web.
ScienceDirect.
Keywords: Neurosciences. -- Encyclopedias; neurotieteet; hermosto